Responses of Photosynthetic and Defence Systems to High Temperature Stress in Quercus suber L Seedlings Grown under Elevated CO2 - FARIA, T.; Vaz, M.; Schwanz, P.; PolIe, A. (Plant biology (Stuttgart, Germany), 2008)
Growth in elevated CO2 led to an increase in biomass production per plant as a result of enhanced carbon uptake and lower rates of respiration, compared to ambient C02-grown plants. No down-regulation of photosynthesis was found after six months of growth under elevated CO2. Photosynthetic rates at 15°C or 35°C were also higher in elevated than in ambient C02-grown plants, when measured at their respective CO2 growth condition. Stomata of elevated C02-grown plants were less responsive to temperature as compared to ambient CO2 plants. The after effect of a heat-shock treatment (4 h at 45°C in a chamber with 80% of relative humidity and 800—1000 tmol rn2 photon flux density) on Amax was less in elevated than in ambient C02-grown plants. At the photochemical level, the negative effect of the heat-shock treatment was slightly more pronounced in ambient than in elevated CO2-grown plants. A greater tolerance to oxidative stress caused by high temperatures in elevated C02-grown plants, in comparison to ambient CO2 plants, is suggested by the increase in superoxide dismutase activity, after 1 h at 45°C, as well as its relatively high activity after 2 and 4 h of the heat shock in the elevated C02-grown plants in contrast with the decrease to residual levels of superoxide dismutase activity in ambient C02-grown plants immediately after 1 h at 45°C. The observed increase in catalase after 1 h at 45°C in both ambient and elevated C02-grown plants, can be ascribed to the higher rates of photorespiration and respiration under this high temperature.
Keywords: catalase; Elevated CO2; photosynthesis; Quercus suber L.; superoxide dismutase; Temperature

How Plants Cope with Water Stress in the Field? Photosynthesis and Growth - Chaves, M. M.; Pereira, J. S.; MAROCO, J.; Rodrigues, M. L.; RICARDO, C. P. P.; OSÓRIO, M. L.; CARVALHO, I.; FARIA, T.; PINHEIRO, C. (Annals of Botany, 2002)
Plants are often subjected to periods of soil and atmospheric water deficit during their life cycle. The frequency of such phenomena is likely to increase in the future even outside today’s arid/semi‐arid regions. Plant responses to water scarcity are complex, involving deleterious and/or adaptive changes, and under field conditions these responses can be synergistically or antagonistically modified by the superimposition of other stresses. This complexity is illustrated using examples of woody and herbaceous species mostly from Mediterranean‐type ecosystems, with strategies ranging from drought‐avoidance, as in winter/spring annuals or in deep‐rooted perennials, to the stress resistance of sclerophylls. Differences among species that can be traced to different capacities for water acquisition, rather than to differences in metabolism at a given water status, are described. Changes in the root : shoot ratio or the temporary accumulation of reserves in the stem are accompanied by alterations in nitrogen and carbon metabolism, the fine regulation of which is still largely unknown. At the leaf level, the dissipation of excitation energy through processes other than photosynthetic C‐metabolism is an important defence mechanism under conditions of water stress and is accompanied by down‐regulation of photochemistry and, in the longer term, of carbon metabolism.
10.1093/aob/mcf10510.1093/aob/mcf105
Keywords: carbon assimilation; high temperature; Lupinus; photosynthesis; Quercus ilex; Quercus suber; stomatal functioning; Stress; Vitis vinifera; water-stress; xanthophyll cycle

Photochemical response to summer drought in Quercus ilex trees growing in a naturally CO2 enriched site - FARIA, T.; Cerasoli, S.; García-Plazaola, J. I.; Guimaraes, M. P.; Abadia, A.; Raschi, A.; Miglietta, F.; Pereira, J. S.; Chaves, M. M. (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
The effect of the interaction between water stress and growth at elevated CO2 on the leaf photochemistry were studied in Quercus ilex trees, growing in a naturally CO2 enriched site (the Bossoleto, Italy). Those plants were compared with plants growing nearby in similar soils but at ambient CO2 concentration. Our data indicate that down-regulation of photosynthesis is lower in non-watered trees from the enriched site than in non-watered trees from the ambient-CO2 site This may be associated to the higher carbon availability for the consumption of the excess absorbed light energy or to an increased protection of the photochemical apparatus against oxidative stress in plants grown under elevated CO2.
The following values have no corresponding Zotero field: periodical: IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS pub-location: PO BOX 17, 3300 AA DORDRECHT, NETHERLANDS
Keywords: Elevated CO2; fluorescence; water stress; xanthophylls

Seasonal changes in xanthophyll composition and photosynthesis of cork oak (Quercus suber L.) leaves under mediterranean climate - García-Plazaola, J. I.; FARIA, T.; Abadía, J.; Chaves, M. M.; Pereira, J. S. (Journal of Experimental Botany, 1997)
Seasonal changes in pigment composition of sun and shade leaves of cork oak (Quercus suber) were studied under field conditions in Portugal. Expanding leaves showed a high concentration of xanthophyll cycle components, violaxanthin, antheraxanthin and zeaxanthin. The pool of violaxanthin plus antheraxanthin plus zeaxanthin (V+A+Z) varied greatly between the seasons, being higher at the end of summer and in winter when photosynthesis was limited by water stress and cold, respectively. The size of V+A+Z pool was associated to synthesis of zeaxanthin in response to an excess of light. In sun leaves, midday A+Z relative content was positively correlated with the V+A+Z pool, whereas in shade leaves A+Z decreased with leaf ageing. In both leaf types A+Z was positively correlated with the non-photochemical quenching (NPQ) of chlorophyll a fluorescence. However, in winter NPQ did not change significantly throughout the day, whereas the (A+Z)/(V+A+Z) increased following the typical daily trend observed in other seasons.
10.1093/jxb/48.9.166710.1093/jxb/48.9.1667
Keywords: chlorophyll fluorescence; pigments; Quercus suber; thermal dissipation; xanthophylls

Growth at elevated CO2 leads to down-regulation of photosynthesis and altered response to high temperature in Quercus suber L. seedlings - FARIA, T.; Wilkins, D.; Besford, R. T.; Vaz, M.; Pereira, J. S.; Chaves, M. M. (Journal of Experimental Botany, 1996)
The effects of growth at elevated CO2 on the response to high temperatures in terms of carbon assimilation (net photosynthesis, stomatal conductance, amount and activity of Rubisco, and concentrations of total soluble sugars and starch) and of photochemistry (for example, the efficiency of excitation energy captured by open photosystem II reaction centres) were studied in cork oak (Quercus suber L.). Plants grown in elevated CO2 (700 ppm) showed a down-regulation of photosynthesis and had lower amounts and activity of Rubisco than plants grown at ambient CO2 (350 ppm), after 14 months in the greenhouse. At that time plants were subjected to a heat-shock treatment (4 h at 45°C in a chamber with 80% relative humidity and 800–1000 µmol m−2 s−1 photon flux density). Growth in a CO2-enriched atmosphere seems to protect cork oak leaves from the short-term effects of high temperature. Elevated CO2 plants had positive net carbon uptake rates during the heat shock treatment whereas plants grown at ambient CO2 showed negative rates. Moreover, recovery was faster in high CO2-grown plants which, after 30 min at 25°C, exhibited higher net carbon uptake rates and lower decreases in photosynthetic capacity (Amax as well as in the efficiency of excitation energy captured by open photosystem II reaction centres (FvJFm than plants grown at ambient CO2. The stomata of elevated CO2 plants were also less responsive when exposed to high temperature.
10.1093/jxb/47.11.175510.1093/jxb/47.11.1755
Keywords: acclimation; Elevated CO2; photo- synthesis; Quercus suber L.; Temperature